2007
DOI: 10.1016/j.molimm.2006.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the central complement component C3

Abstract: C3 is a central protein of the complement system, which is important to immune defense and provides a link between innate and adaptive immunity. Three pathways of complement activation converge at the activation of C3 yielding a diverse set of biological responses. This versatile and flexible molecule interacts with various proteins to fulfill its functions. Here we review recent insights gained from the crystal structure determinations of human, native C3 and its physiological down-regulation product C3c. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
44
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 67 publications
(51 reference statements)
1
44
0
2
Order By: Relevance
“…SCR2 and SCR3 of Ba were packed tightly into an antiparallel dimer capped by SCR1 (6). These structural data also indicate that SCR1 probably hinders access of the ligand C3b to the MIDAS of the vWA domain, and that the triad of SCR domains is probably only weakly associated with the vWA and SP domains.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…SCR2 and SCR3 of Ba were packed tightly into an antiparallel dimer capped by SCR1 (6). These structural data also indicate that SCR1 probably hinders access of the ligand C3b to the MIDAS of the vWA domain, and that the triad of SCR domains is probably only weakly associated with the vWA and SP domains.…”
mentioning
confidence: 69%
“…The ␣ЈNT and C345C domains in C3b include putative binding sites for fB required for C3 convertase formation (3)(4)(5). Both the ␣ЈNT and C345C domains are located in a part of the C3 molecule that undergoes large rearrangements upon activation of C3 into C3b, which explains why C3 does not interact with fB (6). Similarly, structural analyses have suggested that formation of the AP C3-convertase probably depends on the structure and orientation of the CUB domain of C3b and that the interaction between C3b and fB is independent of the TED domain (7).…”
mentioning
confidence: 99%
“…19 Activation of the classical, lectin, and alternative pathways results in cleavage of C3 to generate C3b and the anaphylatoxin C3a. When C3b is produced, the thioester is cleaved, and then this highly reactive species may bind covalently to targets.…”
Section: C3mentioning
confidence: 99%
“…The CP, LP, and AP each induce assembly of C3 convertases that cleave complement component C3 to C3b, exposing a thioester domain that rapidly undergoes covalent linkage to hydroxyl or amine groups (7). In this way, C3b can become tethered to nearby surfaces.…”
mentioning
confidence: 99%